2015
DOI: 10.3109/0284186x.2015.1049661
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver variation among pathologists for delineation of tumor on H&E-sections of laryngeal and hypopharyngeal carcinoma. How good is the gold standard?

Abstract: P. J. Raaijmakers (2016) Interobserver variation among pathologists for delineation of tumor on H&E-sections of laryngeal and hypopharyngeal carcinoma. How good is the gold standard?, Acta Oncologica, 55:3, 391-395,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…We observed that the HE-based tumor delineations were comparable to the CK-AE1/3-based tumor delineations within two millimeters. The variation between both tumor delineations, quantified using the conformity index (CI), was comparable to the interobserver variation on HE-based tumor delineations as determined by Jager et al who reported a CI of 0.87 [18] .…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…We observed that the HE-based tumor delineations were comparable to the CK-AE1/3-based tumor delineations within two millimeters. The variation between both tumor delineations, quantified using the conformity index (CI), was comparable to the interobserver variation on HE-based tumor delineations as determined by Jager et al who reported a CI of 0.87 [18] .…”
Section: Discussionsupporting
confidence: 64%
“…We also found these discrepancies between HE and cytokeratin based delineations. The discrepancy in delineations for tumor invaded cartilage is in correspondence with the high interobserver variation for delineation of cartilage invasion on HE stained sections [18] . We observed that the tumor tissue was sometimes discontinuously infiltrating the bone marrow and that background staining was high in this area for CK-AE1/3; both might have resulted in the variation between HE and CK-AE1/3 based delineations in the cartilage.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In general, the interobserver variation between pathologists was small [15]. However, the irregular shape of this tumor, with a large amount of swelling around the tumor, hampered an accurate delineation on both the H&E sections and the MR images.…”
Section: Discussionmentioning
confidence: 90%